Pola Pengembangan Rumah di Kampung Kota dan Faktor-Faktor yang Mempengaruhinya - Nurdiani, Nina (Bina Nusantara University, 2010)
The housing development is done by city kampong society self-supportingly at its growth become very difficult to be controlled. To make sustainable environment in city kampong hence require to be done a research concerning Pattern of Housing Development in City Kampong and the Factors Its Influence. This research used Descriptive-Analytical research method and take case study in Bidara Cina Kampong, Bidara Cina sub-district, Jatinegara district, East Jakarta. Result of this research indicates that the increasing of prosperity of society in city kampong which generally is middle income society to low income tend to be accompanied by degradation of environmental quality of its settlement. This condition happened because ably limited economics and very the limited wide of land of private. The kampong society tending to develop bedroom and living room as multi function room, and at the process development of house heedless of neighbors environment. Dominant factors influence pattern of housing development in city kampong alternately is social-culture factors, condition of physical land and house factors, economics factors, requirement of human being factors, and non-physical factors (legality of land and house).